2020
DOI: 10.3389/fnmol.2019.00318
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis of Pineal Glands in the Mouse Model of Alzheimer’s Disease

Abstract: The pineal gland maintains the circadian rhythm in the body by secreting the hormone melatonin. Alzheimer's disease (AD) is the most common neurodegenerative disease. Pineal gland impairment in AD is widely observed, but no study to date has analyzed the transcriptome in the pineal glands of AD. To establish resources for the study on pineal gland dysfunction in AD, we performed a transcriptome analysis of the pineal glands of AD model mice and compared them to those of wild type mice. We identified the global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…However, studies of circRNAs in the rat pineal gland have rarely been reported. Only one study reported significant differences in circRNA expression in the pineal gland of AD mice 43 . Therefore, in our study, RNA-seq was used to identify and detect the expression of mRNAs, circRNAs and miRNAs in the rat pineal gland between day and night.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies of circRNAs in the rat pineal gland have rarely been reported. Only one study reported significant differences in circRNA expression in the pineal gland of AD mice 43 . Therefore, in our study, RNA-seq was used to identify and detect the expression of mRNAs, circRNAs and miRNAs in the rat pineal gland between day and night.…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG pathway analysis revealed several important pathways related to the circadian clock, including the PI3K-Akt signaling pathway, adrenergic signaling in cardiomyocytes and cGMP-PKG signaling pathway. The PI3K-Akt signaling pathway has been shown to be regulated by the clock proteins Cry1, Cry2 and Bmal1, which are part of the oscillations of the transcriptional-translational negative feedback system and regulate the circadian rhythm 43 , 47 , 48 . Mustafa C Beker reported an interaction of melatonin and Bmal1 in the regulation of PI3K/AKT pathway components and cellular survival 49 .…”
Section: Discussionmentioning
confidence: 99%
“… 51 , 52 We combined the results obtained from the two algorithms to increase the reliability of the lncRNAs selection procedure as previously reported. 53 …”
Section: Methodsmentioning
confidence: 99%
“…CREB is an important transcriptional factor in the regulation of brain-derived neurotrophic factor (BDNF) and with the CREB-BDNF signaling pathway modulating cognitive status and Aβ toxicity in AD [ 172 ]. In the pineal gland of 5xFAD mice, Nam et al [ 105 ] constructed a circRNA-miRNA network with the 10 circRNAs whose expression differences were more significant or whose expression levels were high. From it, a complete ceRNET was established, where circMboat2 and circNlrp5-ps could sponge miR-483 and regulate the expression of Aanat , a critical enzyme for melatonin synthesis [ 173 ].…”
Section: Cerna Network and Neurodegenerative Diseasesmentioning
confidence: 99%